North European gall-inducing Euura sawflies (Hymenoptera, Tenthredinidae, Nematinae) - Liston, Andrew D.; Heibo, Erik; Prous, Marko; Vårdal, Hege; Nyman, Tommi; Vikberg, Veli (Zootaxa, 2017)
The sawfly genus Euura of the tenthredinid subfamily Nematinae, in which species level taxonomy has long been regarded as controversial, is particularly species rich in northern parts of the Holarctic. Among a majority of species with more or less free-living larvae, a sizeable minority belongs to a monophyletic lineage whose larvae complete their whole development in galls. We present illustrated keys to the adults and galls of 66 gall-inducing Euura species that occur, or might occur, in northern Europe. The distribution of these species is briefly reviewed, with an emphasis on the fauna of Sweden, where 55 species are now definitely recorded, two of them for the first time (E. bigallae, E. myrtilloidica). The species-level taxonomy of gall-inducing Euura remains partly problematic. Nominal species described on the basis of experimentally tested or assumed host plant specificity, but which cannot be recognised using morphological or genetic characters, are treated as conspecific with currently indistinguishable segregates ("host-plant races") associated with other Salix species. 20 new synonymies are proposed (valid names in parentheses): Eupontania acutifoliae baltica Vikberg & Zinovjev, 2006 and Pontania acutifoliae daphnoides Zinovjev, 1993 (Euura acutifoliae (Zinovjev, 1985)), Euura boreoalpina Kopelke, 2001 (Euura lanatae Malaise, 1921), Euura cinereae Kopelke, 1996 preoccupied and Euura lapponica Kopelke, 1996 preoccupied (Euura auritae Kopelke 2000), Euura gemmacinereae Kopelke, 2001 and E. nigritarsis Cameron, 1885 (Euura mucronata (Hartig, 1837)), Euura phylicifoliae Kopelke, 2001 (Euura myrsinifoliae Kopelke, 2001), Nematus westermanni Boheman, 1852 nomen oblitum (Euura scotaspis (Förster, 1854) nomen protectum), Nematus acerosus Hartig, 1840 (Euura saliciscinereae (Retzius, 1783)), Nematus alienatus Förster, 1854 and Phyllocolpa rolleri Liston, 2005 (Euura leucapsis (Tischbein, 1846)), Nematus angustus Hartig, 1837 (Euura atra (Jurine, 1807)), Nematus erythropygus Förster, 1854 (Euura leucosticta (Hartig, 1837)), Nematus impunctatus Herrich-Schäffer, 1840 (Euura amerinae (Linnaeus, 1758)), Pontania carinifrons Benson, 1940 and Phyllocolpa plicaglauca Kopelke, 2007 (Euura destricta (MacGillivray, 1923)), Pontania obscura Kopelke, 2005 (Euura bridgmanii (Cameron, 1883)), Pontania viminalis var. lugubris Enslin, 1918 and Eupontania collactanea rosmarinifoliae Vikberg & Zinovjev, 2006 (Euura collactanea (Förster, 1854)). Euura weiffenbachiella nom. nov. is proposed as a replacement name for Euura weiffenbachii Ermolenko, 1988; preoccupied in Euura by Pteronidea weiffenbachi Lindqvist, 1958 (Euura piliserra (Thomson, 1863)). Lectotypes are designated for the following 9 taxa: Euura insularis Kincaid, 1900, Euura lanatae Malaise, 1921, Euura lappo Malaise, 1921, Euura lappo var. hastatae Malaise, 1921, Nematus acerosus Hartig, 1840, Nematus leptocerus Förster, 1854, Nematus vallisnierii Hartig, 1837, Pontania megacephala Rohwer, 1908, and Pontania piliserra var. mascula Enslin, 1915. Because of secondary homonymy within Euura, the valid name of the Nearctic species E. arctica MacGillivray, 1919 is E. delicatula (MacGillivray, 1919). The Nearctic Euura megacephala is removed from synonymy with the Holarctic E. destricta and treated as a valid species. 34 species names are newly combined with Euura.